English Talks for Business Communication: The Use of Free4talk in Vocational Education - Surya Setiadi Tarigan (JALL (Journal of Applied Linguistics and Literacy), 2026)
The rapid digital transformation in the Industry 4.0 era has reshaped vocational education, emphasizing the need for graduates who possess strong English communication skills aligned with global business demands. This study investigates students’ perceptions of using Free4Talk, an online language exchange platform, to enhance English for Business Communication among vocational students. Employing a mixed method design, the research collected quantitative data through a five point Likert scale questionnaire and qualitative data through semi-structured interviews with 20 Business Administration students at Kupang State Polytechnic. Descriptive statistics were used to analyze the questionnaire, while thematic analysis was applied to interpret interview responses. The findings revealed that students hold positive perceptions of Free4Talk across four key dimensions: usability and accessibility (M=3.73), motivation and engagement (M=3.59), language and business communication skills (M=3.45), and intercultural communication competence (M=3.43) all categorized as “high.” The results indicate that Free4Talk effectively fosters speaking fluency, confidence, and intercultural awareness through authentic, real time interaction with global users. Students valued its accessibility, user friendly design, and motivational features that encouraged frequent speaking practice beyond the classroom. In conclusion, integrating Free4Talk into vocational English instruction bridges academic and workplace communication needs, supporting the development of globally competent communicators. It is recommended that future research employ experimental or longitudinal approaches to examine measurable gains in fluency, accuracy, and pragmatic competence, as well as to explore the integration of teacher guidance and feedback mechanisms in technology-mediated language learning